Hydrogen-induced degradation of high-strength steel pipeline welds: A critical review. (March 2022) - Sun, Yinghao; Frank Cheng, Y.
Highlights: Reviewed the fundamentals of hydrogen permeation, diffusion and trapping at pipeline welds. Discussed the effect of welding metallurgy of high-strength steels on hydrogen degradation. Proposed new research techniques for hydrogen degradation at pipeline welds. Abstract: High-strength steel pipeline technology has been developing in the past decade in response to rapidly increasing energy demand. The unique metallurgical microstructure at pipeline welds, which is combined with a synergism of hydrogen and stress, makes the area prone to hydrogen-induced degradation, resulting in pipeline failure. This work developed a comprehensive review on hydrogen permeation, diffusion and trapping, as well as the resulting hydrogen degradation at pipeline welds. While major efforts have been made to study the hydrogen degradation behavior, there is still a big space on further investigation and understanding of the problem, especially for the high-strength steel welds. Conventional testing techniques are difficult to obtain convincing results to understand the mechanism for hydrogen degradation, especially at an atomic scale. Modern computational and modeling techniques provide promising alternatives to define the hydrogen diffusion and trapping and the pipeline degradation at the welds. It is expected that a combination of computational modeling and material characterization with an improved spatial resolution can advance our understanding about the hydrogen degradation of the high-strength steel pipeline welds.